Google web toolkit for Ajax - Perry, Bruce W. (O'Reilly, 2006)
The Google Web Toolkit (GWT) is a nifty framework that Java programmers can use to create Ajax applications. The GWT allows you to create an Ajax application in your favorite IDE, such as IntelliJ IDEA or Eclipse, using paradigms and mechanisms similar to programming a Java Swing application. After you code the application in Java, the GWT's tools generate the JavaScript code the application needs. You can also use typical Java project tools such as JUnit and Ant when creating GWT applications. The GWT is a free download, and you can freely distribute the client- and server-side code you c.